CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Simplify and solve the following linear equation

3(5z_7)_2(9z_11)=4(8z_13)_17


Solution

3(5z – 7) – 2(9z – 11) = 4(8z – 13) – 17
This is our question
Multiply each bracket with the number outside it.For example multiply (5z-7) with 3.
Thus we get the equation as
15z – 21 – 18z + 22 = 32z – 52 –17

Here we have to solve for z. So,take all the terms with z to one side and the numbers to the other side.If we rearrange like that we get,

15z – 18z–32z =  – 52 –17–22+21 
-35z = -70
z = begin mathsize 12px style fraction numerator negative 70 over denominator negative 35 end fraction equals space 2 end style
z = 2 is the solution for the given linear equation. 

 

flag
 Suggest corrections
thumbs-up
 
0 Upvotes


Similar questions
View More


People also searched for
View More



footer-image